Degree of Formality: Analyses of Linguistic Deviations in a Facebook Status and Comments Section - Aisyah Khaleeda, Rosli; Noor Raha, Mohd Radzuan (Penerbit UMP, 2022)
Social network has become the new ‘news outlet’ for today’s generation. However, users of social networks are notbound to any linguistics rules, especially when posting statuses. Hence, this paper aimed to identify the degree of formality and informality used in a Facebook status posted by an Indian public figure by looking at the occurrence of linguistic deviations in sentences, specifically in the post itself and the comments section. This research utilized a qualitative method where manual extraction of public user-generated textual data are collected and analysed via content analysis. A total of 1,023 words were analysed. The result of the research reflects the English language competency of Facebook users in an online communication with a public figure. The occurrences of linguistic deviations in the comments section also proved that the deviations are comprehensible, understood and accepted among the users, as long as the meanings of the messages were maintained and conveyed. Although the occurrences of linguistic deviation in this study found a pattern of informality in the online communication when conversing with a public figure or the people with power, it suggested the closeness and friendliness between the two respective groups. The findings of the study can be used to improve the pedagogy of communication English and expand the knowledge in the field of theory of linguistic deviation.